Knowledge Requirement of Incorporating Artificial Intelligence in Engineering Education through TPACK (Asean Journal of Engineering Education, 2023)
It is believed that Malaysians have no interest in the field of engineering education. Engineering curriculum development and educator development are neglected. As a result, most of engineering educators deliver the contents lack or without pedagogical knowledge. It becomes worst when they incorporate artificial intelligent applications in their classrooms without pedagogical knowledge. Therefore, this work is to create awareness among engineering educators about the knowledge that they need before using artificial intelligence in their classroom. The first author describes her experienced incorporating technology/artificial intelligence in engineering education. She discussed initial knowledge that engineering educators need before they are capable to teach a subject using artificial intelligence based on Technological, Pedagogical and Content Knowledge (TPACK) framework. However, this knowledge alone may not be translated into quality teaching. Therefore, the first author discussed Community of Inquiry (CoI) and she believes that CoI is a venue for engineering educators to simulate the knowledge. As a conclusion, TPACK can be modelled as engineering educators’ professional knowledge and CoI as assessment method.
Keywords: Technology knowledge; Pedagogy knowledge; Content knowledge; Engineering education; Community of Inquiry